Rosai–Dorfman disease presenting as a scleral nodule in a female with multisystem inflammatory syndrome post-COVID-19 infection - Nashra Alma; Smitha Kuthyar Shambu; Kalpana Babu (Taiwan Journal of Ophthalmology)
We report a rare presentation of Rosai–Dorfman disease (RDD) as scleritis transforming to a nodule in a female with multisystem inflammatory syndrome following COVID-19 infection. A 54-year-old female presented to us first in August 2022 with redness and slight discomfort in both eyes of 2 weeks’ duration. She had a history of multisystem inflammatory syndrome post-COVID-19 infection. Although she presented with scleritis (oculus uterque), it continued to persist with a course of oral and topical steroids. Laboratory investigations including autoimmune profile were negative. Only QuantiFERON-TB Gold test was positive. High-resolution computed tomography showed a few subcentimeter enlarged mediastinal lymph nodes and a cluster of enlarged cervical lymph nodes. Biopsy showed chronic granulomatous inflammation with no caseation, negative for Mycobacterium tuberculosis. Over a year, this transformed to a scleral nodule. Excision biopsy confirmed RDD disease. Whole body positron emission tomography-computerized tomography confirmed no active lesions elsewhere. She was started on methotrexate. At 1-year follow-up, there was no recurrence.